แนวทางการพัฒนาครูของโรงเรียนอนุบาลนานาชาติเพรพ ตามแนวคิดการเรียนรู้ที่ชัดแจ้ง - ลีลาปัญญาเลิศ, ธิติดา; เจริญกุล, นันทรัตน์ (An Online Journal of Education, 2018)
The purpose of this research were to study 1) the current education management at Prep International Kindergarten based on the visible learning framework and 2) to propose management strategies for developing teacher development program. The research was a case study using a mixed method approach. The sample population consisted of Sutthisarn & Ladprao campuses. The respondents are 1 head teacher, 2 Thai principals and all teachers (13). The main instruments of this research were a semi-structured interview and a rating scaled questionnaire. The statistics used were frequency, mean, percentage, standard deviation, PNI and content analysis. The results concerning the visible learning framework with 7 perspectives’ revealed that 1) All adults were passionate & inspired and vigilant about create positive affects on achievement for students; 2) The school provided development program to help teachers seek pathways towards showing passion for teaching & learning; 3) When planning lesson, teachers invoked appropriate challenges that engage the students’ commitment; 4) The climate of starting lesson provided high value of trust; 5) Teachers applied multiple assessment methods to provide feedback to students; 6) Students felt respect, trust, optimism and welcomed into class; 7) School leaders and teachers believed it was their roles to develop positive relationships in school. The management strategies are 1) The school sets clear objective on visible learning; 2) School provides training and coaching program for teachers; 3) The management use rubrics in to measure teacher's performance.